A case of oral lichenoid reaction during nivolumab therapy. Issue 6 (November 2020) - Yamanaka, Shigeki; Nakao, Kazumasa; Ninomiya, Aya; Watanabe, Takuma; Inoue, Yu; Kashiwagi, Marina; Fukuhara, Shizuko; Asai, Keita; Yamaguchi, Akihiko; Kataoka, Tatsuki; Bessho, Kazuhisa
Abstract: Nivolumab is a monoclonal antibody drug targeting the programmed cell death receptor-1 (PD-1). It has been shown to improve immune responses and marked clinical efficacy to treat many cancers such as advanced melanoma and non-small-cell lung cancer. However, immune-related adverse events (irAEs) in multiple organ systems are a well-recognized consequence of immunotherapy. Previous reports show that oral lichenoid reactions (OLRs) have been observed in patients receiving anti-programmed death cell receptor-1 therapy such as nivolumab. Here we report a case of OLR presenting with white lesions associated with nivolumab therapy. A 26-year-old woman was administered nivolumab for stage IIIC melanoma of the lower back and developed asymptomatic white lesions on her buccal mucosa, seven weeks after the initial nivolumab therapy. She was diagnosed with OLR based on these clinical and histopathological features, which were similar to graft-versus-host reactions. The patient responded well to topical dexamethasone and she continued nivolumab therapy.